Low sensitivity of conventional fungal agars in fungemia by Rhodotorula mucilaginosa: description of two cases - Carmen Alicia Garcia-Gutiérrez; María Soledad Cuétara-García; María Dolores Moragues; Jorge Ligero; Sara María Quevedo; María José Buitrago (BMC, 2021)
Abstract Background Although most bloodstream yeast infections are caused by Candida spp., infections by rare or less common species have increased in recent years. Diagnosis of infections caused by these species is difficult due to the lack of specific symptoms and adequate diagnostic tools. Cases presentation We describe two cases of fungemia by Rhodotorula mucilaginosa within a few months of each other, in a secondary Spanish hospital. In both cases, diagnosis was challenging. Blood subcultures in conventional fungal media were persistently negatives and the use of non-conventional fungal media was essential for isolating the yeasts and achieving a correct diagnosis. 1-3 beta-d-glucan detection and a panfungal PCR assay were helpful techniques to confirm the diagnosis Conclusion It is highly important to establish an early diagnosis for fungemia. The process is challenging because often non-specific symptoms are presents. When yeasts grow in blood cultures other genera than Candida spp. could be the cause of infection. Patient risk factors should be assessed to incorporate alternative culture media and the available rapid diagnostic test, in order to provide an early recognition of the pathogen.